C35 Hopanoid Side Chain Biosynthesis: Reduction of Ribosylhopane into Bacteriohopanetetrol by a Cell‐Free System Derived from Methylobacterium organophilum. Issue 12 (14th July 2015) - Bodlenner, Anne; Liu, Wenjun; Hirsch, Guillaume; Schaeffer, Philippe; Blumenberg, Martin; Lendt, Ralf; Tritsch, Denis; Michaelis, Walter; Rohmer, Michel
Abstract The major bacterial triterpenoids of the hopane series each consist of a C30 triterpene hopane moiety and an additional nonterpene C5 side chain derived from D‐ribose and linked through its C‐5 carbon atom to the hopane side chain. Bacteriohopanetetrol and aminobacteriohopanetriol are the most common representatives of this natural product series, adenosylhopane and ribosylhopane being putative precursors. Deuterium‐labelled ribosylhopane was obtained by hemisynthesis and converted into deuterium‐labelled bacteriohopanetetrol in the presence of NADPH, thus giving evidence of this as yet unknown precursor‐to‐product relationship in the bacterial hopanoid metabolic pathway.